Frailty in patients undergoing transcatheter aortic valve implantation: a protocol for a systematic review. Issue 2 (5th February 2019) - Li, Zhe; Dawson, Emily; Moodie, Jessica; Martin, Janet; Bagur, Rodrigo; Cheng, Davy; Kiaii, Bob; John-Baptiste, Ava
Abstract : Introduction: Aortic stenosis is a significant cause of morbidity and mortality in older patients. The advent of transcatheter aortic valve implantation (TAVI) offers an alternative to surgical aortic valve replacement for patients with severe symptomatic aortic stenosis who are at high or intermediate risk of adverse events. Existing evidence highlights the importance of frailty as a predictor of poor outcomes post-TAVI. The objective of this study is to review the operationalisation of frailty instruments for TAVI recipients and determine clinical outcomes and the change in quality of life in frail patients undergoing TAVI. Methods and analysis: Methods are reported according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2015 checklist. We will search relevant databases to identify published, completed but unpublished and ongoing studies. We will include studies of patients with aortic stenosis, diagnosed as frail and who underwent a TAVI procedure that report mortality, clinical outcomes or health-related quality of life. Retrospective or prospective cohort studies, randomised controlled trials and non-randomised controlled trials will be eligible for inclusion. Two researchers will independently screen articles for inclusion, with disagreements resolved by a third reviewer. One researcher will extract data with audit by a second researcher. The risk of bias in studies will be evaluated using the Quality in Prognosis Studies tool. Meta-analysis of mortality, survival curve and the change in quality of life will be performed if appropriate. Subgroup analysis, sensitivity analysis and meta-regression will be performed if necessary. Ethics and dissemination: Due to the nature of this study, no ethical issues are foreseen. We will disseminate the results of our systematic review through a peer-reviewed journal. Trial registration number: CRD42018090597.